Bystander monocytic cells drive infection-independent NLRP3 inflammasome response to SARS-CoV-2 - Leon L. Hsieh; Monika Looney; Alexis Figueroa; Guido Massaccesi; Georgia Stavrakis; Eduardo U. Anaya; Franco R. D'Alessio; Alvaro A. Ordonez; Andrew S. Pekosz; Victor R. DeFilippis; Petros C. Karakousis; Andrew H. Karaba; et al. (mBio)
ABSTRACT The pathogenesis of COVID-19 is associated with a hyperinflammatory immune response. Monocytes and macrophages play a central role in this hyperinflammatory response to SARS-CoV-2. NLRP3 inflammasome activation has been observed in monocytes of patients with COVID-19, but the mechanism and consequences of inflammasome activation require further investigation. In this study, we inoculated a macrophage-like THP-1 cell line, primary differentiated human nasal epithelial cell (hNEC) cultures, and primary monocytes with SARS-CoV-2. We found that the activation of the NLRP3 inflammasome in macrophages does not rely on viral replication, receptor-mediated entry, or actin-dependent entry. SARS-CoV-2 productively infected hNEC cultures without triggering the production of inflammasome cytokines IL-18 and IL-1β. Importantly, these cytokines did not inhibit viral replication in hNEC cultures. SARS-CoV-2 inoculation of primary monocytes led to inflammasome activation and induced a macrophage phenotype in these cells. Monocytic cells from bronchoalveolar lavage (BAL) fluid, but not from peripheral blood, of patients with COVID-19, showed evidence of inflammasome activation, expressed the proinflammatory marker CD11b, and displayed oxidative burst. These findings highlight the central role of activated macrophages, as a result of direct viral sensing, in COVID-19 and support the inhibition of IL-1β and IL-18 as potential therapeutic strategies to reduce immunopathology without increasing viral replication.IMPORTANCEInflammasome activation is associated with severe COVID-19. The impact of inflammasome activation on viral replication and mechanistic details of this activation are not clarified. This study advances our understanding of the role of inflammasome activation in macrophages by identifying TLR2, NLRP3, ASC, and caspase-1 as dependent factors in this activation. Further, it highlights that SARS-CoV-2 inflammasome activation is not a feature of nasal epithelial cells but rather activation of bystander macrophages in the airway. Finally, we demonstrate that two pro inflammatory cytokines produced by inflammasome activation, IL-18 and IL-1β, do not restrict viral replication and are potential targets to ameliorate pathological inflammation in severe COVID-19.